PENERBITAN MAJALAH DI KELANTAN: ANALISIS TULISAN DATO’ YUSOFF ZAKY DALAM MAJALAH PENGASUH (Publication of Magazines in Kelantan: Analysis of Dato’ Yusoff Zaky’s Writing in Pengasuh) - Abdul Hamid, Faisal @ Ahmad Faisal (Journal of Al-Tamaddun, 2018)
Pengasuh is a magazine that covers writings of religious scholars since the beginning of its publication until nowadays. Hence, this article discusses on two important matters: (1) the development of magazine publications in Kelantan in general and the publication of Pengasuh in particular, (2) Involement of Dato’ Yusoff Zaky in producing his works especially regarding the interpretation of the Quran in Pengasuh, as well as commentary on his style and form of writing. To achieve these objectives, this article discusses the historical background of Pengasuh publication and biography of Dato’ Yusoff Zaky. Furthurmore, it discusses the strengthness of Dato’ Yusoff Zaky’s writing and topics of his writings which have meet the needs of Pengasuh readers during that period. In conclusion, Pengasuh has great influence and reached number of readers including in Singapore, Brunei and Thailand due to Dato’ Yusoff Zaky’s effort in establishing the magazine.